Sistem Informasi Rekam Medis di Klinik dr. Yosefa Lily Londa Berbasis Web - Rusmini Faisal (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
The rapid advancement of information technology has significantly influenced various sectors, including healthcare. Clinics, as frontline healthcare providers, are increasingly required to improve their service quality by adopting efficient and integrated information systems. One of the most vital components of healthcare information is medical records, which serve as the foundation for accurate diagnosis, treatment planning, and continuity of care. However, many clinics still rely on traditional manual recording systems, leading to inefficiencies, frequent errors, and difficulties in retrieving patient data in a timely manner. This study aims to design, develop, and implement a web-based medical record information system at Klinik dr. Yosefa Lili Londa to address these challenges. The development process uses the Waterfall model, which consists of several stages: analysis, design, implementation, and testing. The system is designed to manage key data components including patient information, registration, medical complaints, diagnosis, and reporting. The results of system testing indicate a significant improvement in data accuracy, reduction in recording errors, faster access to patient records, and more efficient clinical workflows. Based on these findings, the implementation of a web-based medical record system proves to be effective in supporting integrated, efficient, and high-quality healthcare services at the clinic level.